No way to live: Women’s experiences of negotiating the family law system in the context of domestic violence - Laing, Lesley (2010)
This report explores women’s experiences of the family law system following their separation from a relationship in which they experienced domestic violence. The research highlights the inadequacies of the current system in protecting women and children from abuse and makes recommendations for legislative and other reforms.St George Domestic Violence Committee; South Eastern Sydney Illawarra Area Health Service; Benevolent Societ